Beetle-transmitted viruses - Morales, Francisco José; Gamez, R. (International Center for Tropical Agriculture, 1989)
One group of bean diseases with characteristic virus symptoms is the mosaic group, frequently associated with leaf and plant malformations and green and yellow stippling. Insect vectors belong to the families Chrysomelidae, Coccinelidae, and Meloidae. This group of virus contains the bean southern mosaic virus (BSMV), the bean mild mosaic virus (BMMV), the bean rugose mosaic virus (BRMV), the bean pod mottle virus (BPMV), the bean curly dwarf mosaic virus (BCDMV), and the bean yellow stipple virus (BYSV). The geographic distribution, economic importance, host plants, physical properties, purification, transmission, epidemiology, symptomatology, and control measures are given for each one. The symptoms and damage caused by the diseases are illustrated in color. (CIAT)